Green Synthesis, Characterization and Antimicrobial Evaluation of Selenium Nano Particles on Mastitis Causing Bacteria - Debata, Adyasha (Indian Journal of Animal Nutrition, 2021)
Nanotechnology is now creating a growing sense of excitement in the field of life science. Nano particles can be synthesized by chemical, biological and green methods, but green synthesis method is the most emerging approach of preparation due to eco friendly and less time consuming procedure. This study aimed at green synthesis, characterization and evaluation of antibacterial effect of nano selenium on mastitis causing bacteria. Aqueous extract of Coriandrum sativum leaf extract were used for the production of selenium nano particles. Characterization of synthesized nano particles was done by zeta sizer analysis and transmission electron microscope. The result of zeta sizer analysis reveals that the diameters of nano particles are within the range of nano scale i.e. less then 100 nm. Transmission electron microscopy analysis of selenium nano particles was done to confirm the shape, size and morphology. Antibacterial activity of nano minerals was investigated on mastitis causing bacteria such as Escherichia coli and Staphylococcus aureus and Pseudomonas aeruginosa by well diffusion method. The antibiosis test result indicated that selenium nano particles were able to inhibit Escherichia coli and Staphylococcus aureus and Pseudomonas aeruginosa. So, it may be concluded that the advances in nanotechnology has enabled us to utilize particles of nano size of selenium as a therapeutic application against mastitis causing bacteria in the coming years.